Investigating the Impact of Technology Acceptance Factors on Digital Payment Interest - Indana, Rifaatul (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study aims to analyze the factors influencing interest in using digital payment systems by applying the Technology Acceptance Model 2 (TAM 2) approach. The research population consists of students at UIN Sunan Kalijaga Yogyakarta who use digital payment services. Data collection was conducted through an online questionnaire distributed via Google Forms, resulting in a sample of 165 respondents who met the research criteria. The collected data were then analyzed using the SmartPLS 3.0 application to test the proposed hypotheses. The findings reveal that seven out of ten hypotheses were accepted, while three hypotheses were rejected. The study highlights the significant impact of subjective norms, image, job relevance, output quality, and perceived usefulness on students' interest in using digital payments. However, certain variables, such as perceived ease of use, were found to have no significant effect on perceived usefulness. These results provide valuable insights into the factors driving digital payment adoption among students, emphasizing the role of social influence, perceived benefits, and system efficiency. The study contributes to a deeper understanding of digital payment acceptance and offers recommendations for improving adoption strategies.